A comparative study on the feelings of security of homeowners from subdivisions with and without security guards. - Defensor, Leislie Ann Betiwan
This study compared the differences on the feelings of security of homeowners from two different subdivisions as mainly affected by the presence or absence of private security arrangements. Through face-to-face and review of primary and secondary data, this research particularly addressed the following themes: (1) how concern the respondents are about their security situation; (2) the factors that influence the security concern of homeowners and, (3) the effects of the presence of private security forces on their feelings of security., The results showed that the homeowners are generally concerned of their security such that take measures to protect themselves and their properties. These concern for security is drawn from factors such as the type of neighborhood surrounding the subdivisions, the individual economic status of the residents, the crime incidence in the locale and the presence or absence of security providers. As the study was conducted in different location, there exist differences on the strategy for achieving security. Either they cooperate to hire a private security agency or they do not cooperate and rely solely on individual security measures. Notwithstanding the presence of private security arrangement or none, security provision still remains an individual endeavor for each residents. They are all utilizing individual security measures, regardless of the availability of security providers. The type of community where one lives is still the primary factor that leads to each individual's feelings of security, stating the fact that there is no feeling of absolute security. Thus the feelings of security of individual homeowner cannot be determined with the presence of security guards in the subdivision or how visible other security providers are within such vicinity. With each individual having different sources of security threats, which is primarily the community, it is more practical and safe for each homeowner to come-up with individual initiatives to secure themselves and properties from crime, for their security assurance. This study recommended other aspects for further inquiry on individual feelings of security of homeowners such as a casual study on the unreported crimes occurring in the subdivisions and its effects to the feelings of security; a policy analysis on the subdivision rules and regulations on security provision and; looking into other factors that could affect the security situation of homeowners such as the house help.